Survival Differences After Diagnosis of Early-Onset Colorectal Cancer by Race and Ethnicity and Neighborhood-Level Socioeconomic Status - Talar S. Habeshian; Lanfang Xu; Kimberly L. Cannavale; Bernice Batres; Darios Getahun; Chun R. Chao (Journal of Colon And Rectal Cancer, 2026)
Background The incidence of early-onset colorectal cancer (eoCRC), diagnosed at age <50 years, is increasing in the United States. Prior studies using national and state cancer databases have observed higher eoCRC mortality after diagnosis among non-Hispanic Black (NHB) patients. These studies, however, often did not account for insurance status, access to care, and comorbidity burden, which may contribute to the observed disparities. We examined the associations between race and ethnicity and neighborhood-level socioeconomic status (measured by the neighborhood deprivation index (NDI)) and survival among persons with eoCRC in a large integrated healthcare delivery system whose racially/ethnically diverse members have standardized access to care. Methods We included Kaiser Permanente Southern California (KPSC) members diagnosedwith eoCRC (age 15-49 years) between 2009-2020 and followed them through 12/31/2023. Patients with <12 months of prior KPSC membership, an unspecific CRC site, or other/unknown race/ethnicity were excluded. Bivariate and multivariable Cox models were used to estimate hazard ratios (HRs) for the associations between race/ethnicity and NDI and all-cause and CRC-specific mortality. Multivariable models were adjusted for age at diagnosis, sex, Charlson comorbidity score, obesity, stage at diagnosis, cancer site, and histologic subtype. Subgroup analyses were conducted by stage at diagnosis (localized vs. advanced). Results Of 1,695 eoCRC cases included, we observed 465 deaths (among those with known cause, 417 (90.3%) were CRC-specific). The mean follow-up time was 6.8 years. In the adjusted models, NHB and non-Hispanic Asian/Pacific Islander (NH API) patients, but not Hispanic patients, had significantly higher all-cause mortality (HR=1.62, 95% CI: 1.14-2.29; HR=1.44 (1.08-1.93), respectively) compared with non-Hispanic White (NHW) patients. In the subgroup analyses, race and ethnicity were not associated with all-cause mortality among patients with localized disease. However, among patients diagnosed with advanced disease, NHB patients had a significantly higher risk of all-cause mortality compared with NHW patients (HR=1.54, 95% CI: 1.07-2.22, p=0.02). Similar findings were observed for CRC-specific mortality, overall and by cancer stage. NDI was not significantly associated with all-cause or CRC-specific mortality. Conclusions In this insured population, NHB race and ethnicity were associated with increased risk of CRC-specific mortality among those diagnosed with advanced stage eoCRC. However, the number of NHB patients diagnosed at distant stages was small. Therefore, future research is needed to confirm these findings and better understand potential survival disparities.
Keywords: early-onset colorectal cancer